Trening mentalny pomocą w rehabilitacji po operacji – studium przypadku = Mental training in rehabilitation after surgery – case report - Budnik–Przybylska, Dagmara; Przybylski, Jacek (Journal of Education, Health and Sport, 2016)
Budnik–Przybylska Dagmara, Przybylski Jacek. Trening mentalny pomocą w rehabilitacji po operacji – studium przypadku = Mental training in rehabilitation after surgery – case report. Journal of Education, Health and Sport. 2016;6(12):400-411. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.203310 http://ojs.ukw.edu.pl/index.php/johs/article/view/4067 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 14.12.2016. CASE REPORT Trening mentalny pomocą w rehabilitacji po operacji – studium przypadku Mental training in rehabilitation after surgery – case report Dagmara Budnik–Przybylska 1ABDEF, Jacek Przybylski 1ABDEF 1Uniwersytet Gdański, Wydział Nauk Społecznych, ul. Bażyńskiego 4 80-952 Gdańsk, Polska A – study design, B – data collection, C – statistical analysis, D – data interpretation, E – manuscript preparation, F – literature search, G – funds collection. Słowa kluczowe: trening mentalny, kontuzja, rehabilitacja, psychologia sportu Keywords: mental training, injury, rehabilitation, sports psychology Abstract In the sport psychology literature situations of the injuries and dealing with them were described. People are different from each other and differently feel the event that they do occur, including those associated with trauma. The aim of this study was to present the situation of single player - a member of the Polish national sailing team, preparing for the Olympic Games in London in 2012. Streszczenie W literaturze dotyczącej psychologii sportu opisywane były sytuacje kontuzji i radzenia sobie z nimi. Ludzie różnią się między sobą i w różny sposób odczuwają zdarzenia, które im się przytrafiają, w tym również te, związane z urazem. Celem niniejszej pracy było przedstawienie sytuacji zawodniczki - członkini kadry narodowej żeglarstwa, przygotowującej się sportowo pod kątem mentalnym do Igrzysk Olimpijskich w Londynie 2012.